Detoxification in medication-overuse headache, a retrospective controlled follow-up study: Does care by a headache nurse lead to cure?. (February 2016) - Pijpers, JA; Louter, MA; de Bruin, ME; van Zwet, EW; Zitman, FG; Ferrari, MD; Terwindt, GM
Aim: J.A.P. and M.A.L. contributed equally to this manuscript. The aim of this article is to determine whether support by a headache nurse in the treatment of medication-overuse headache (MOH) increases successful withdrawal, and to study determinants of response to withdrawal therapy. Methods: A retrospective, controlled follow-up study was performed with 416 MOH patients. All patients were treated with outpatient withdrawal therapy, with two treatment arms: with or without the support of a specialised headache nurse. The outcome measures were: i) successful withdrawal, defined as discontinuation of all headache medication according to the study protocol; and ii) the responder rate, defined as the percentage of patients with ≥50% reduction in headache days after successful withdrawal and iii) relative reduction in headache days after successful withdrawal. Results: Successful withdrawal percentages were significantly higher in the group supported by the headache nurse than in the group without support (73.1% vs. 60.7%; p = 0.008), which was confirmed in multivariate analysis (OR 1.73, 95% CI 1.11–2.71, p = 0.016). Support by a headache nurse was not associated with response. The underlying primary headache diagnosis, determined after withdrawal, was significantly correlated with response. Conclusion: The support by a headache nurse results in an increased adherence to detoxification.